The structure of responsibility accounting and the usage of its information - Mackevičius, Jonas; Subačienė, Rasa; Tamulevičienė, Daiva (Information & Media, 2016)
In the modern dynamic and competitive business environment, it is essential that the companies seeking to survive in the market and achieve good results would apply responsibility accounting. The issue of the structure of responsibility accounting and the usage of its information – one of the most important management accounting fields – is examined in the article. New definitions of responsibility accounting and responsibility centres as well as a representative scheme of the structure of responsibility accounting are given in the article. The authors have distinguished the following elements of the structure of responsibility accounting: organisational management structure analysis and reorganisation; determination of responsibility accounting goals; establishment of responsibility centres; formation of responsibility centre budgets and self-control of their implementation; evaluation of responsibility centres’ activity; responsibility centres’ accountability to the company's top managers. The principles of the responsibility centres’ establishment, such as decentralization, liberty, subordination, duty, responsibility, and flexibility are analysed in the article. These criteria of the establishment of responsibility centres have been proposed: territorial, organisational, functional, monopolistic, evaluation, accounting and accountability, planning and forecasting. It has been determined by the authors that responsibility centres might be classified according to various features; however, the most important feature is the responsibility fields. Cost, revenue, profit and investment centres might be distinguished by this feature. The information collected and systematized by these features is crucial to the top managers of a company when making operational and long-term management decisions. According to the authors’ opinion, the activity of each responsibility centre should be evaluated in order to determine the results achieved by the centre and the efficiency of resources usage as accurately as possible. For this, both financial and non-financial indicators must be used.The information of cost, revenue, profit and investment centres may be used for finding the solution to various problems. Mostly it is used for the purposes of evaluation of the financial condition and activity results of the company; for the solution of operational and prospective management decisions; disclosure of the activity reserves; forecasting of the company’s activity; detection and evaluation of the company’s risks; determination of the company’s bankruptcy; intensification of the company’s internal controls system, etc.
Keywords: ...